Lean Healthcare in reducing HAI A Systematic Literature Review (Revista do LabDGE - UFF, 2023)
The aim of this study was to analyze the contributions of the Lean Healthcare approach through the use of methods and tools to reduce Healthcare-Associated Infections (HAI). The guiding question of the study was to investigate how can the Lean Healthcare approach contribute to the implementation of actions to mitigate the risk of HealthCare-Associated Infections? Articles were collected from 2010 to February 2021, in the Web of Science, Scopus, Emerald databases. An analysis form was created. Of the 21 articles collected, 09 were selected, according to the PRISMA®. As for Lean Healthcare methods and tools, the use of standardized work, CTQ and SIPOC was identified as the most used to mitigate the risk of HAI. The high LOS of patients in the hospital increases the risk of HAI, with Lean Six Sigma results in the reduction of hospital costs and lower rates of LOS, with the reduction of the number of complications and infections. Standardized work has reduced the rates of HAI, which reinforces the idea of the need to implement the Lean Healthcare approach, with a focus on respect for people and consequently on the valorization of teamwork, which leads to change in the organizational culture.